Melting ice: A hot topic? - Marahatta, Sharadchandra P. (Journal of Agriculture and Environment, 2007)
A review of global melting ice and its causes as well as possible effects has been carried out based on available secondary information. Measured losses due to melting ice have been tabulated and in danger world heritage due to climatic changes were identified. Glaciers, marine bio-diversity, terrestrial bio-diversity, archeological sites and historic cities were considered as the threat of melting ice and it is recommended to look for economic implications and technological options with other possible actions for tackling global warming. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 101-105